1985
DOI: 10.1002/ana.410180607
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome: Associated neurological abnormalities and developmental disabilities

Abstract: The fragile X syndrome is a frequent cause of developmental disabilities. It is associated primarily with nonprogressive X-linked mental retardation. The neurodevelopmental abnormalities of 25 males and 3 females are described. Mental retardation was mild in 4, moderate in 11, severe in 6, and profound in 2 patients, while 4 patients had only learning disabilities. The presence or absence of a developmental disability could not be determined in the youngest (8 months). Seven patients had had infantile autism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Other investigators have also noted the benign course of epilepsy and the good response to the treatment in FXS patients 8,17,[24][25][26] .…”
Section: Discussionmentioning
confidence: 86%
“…Other investigators have also noted the benign course of epilepsy and the good response to the treatment in FXS patients 8,17,[24][25][26] .…”
Section: Discussionmentioning
confidence: 86%
“…29 There are variable figures for the prevalence of seizures depending on the cohort under study. Previous studies recruiting from programs focused on epilepsy and neurology clinics reported a broad range of 14% to 44% prevalence, [30][31][32][33][34][35][36][37][38] and genetics clinics reported an intermediate range of 9% to 27%. [39][40][41][42] Larger studies focused on people with FXS in the community or FXS clinics reported lower prevalence rates overall, ranging from 12% to 18%, 29,[43][44][45] and with higher prevalence for male than for female patients.…”
Section: Neurologic Disordersmentioning
confidence: 99%
“…45 and secondary generalization and status epilepticus can occur. 48,49 Seizures are easily controlled 29,31,36,38,42,45,47 and resolve during childhood in the majority of people with FXS. 43,47 Routine EEG screening of people with FXS is not recommended unless the patient presents with behaviors or episodes that might represent seizures.…”
Section: Neurologic Disordersmentioning
confidence: 99%
“…Various authors reported a 25-40% incidence of seizures (221,222). Generalized tonic-clonic seizures are the most common seizure type.…”
Section: Epileptologymentioning
confidence: 99%